Risk Factor Profile of Lung Cancer Patients: A Study from the Himalayan State of Indian Subcontinent - Manjunath, Sharathbabu N; V. Madabhavi, Irappa; S. Sarkar, Malay; S. Kaushal, Satinder (Asian Pacific Journal of Cancer Care, 2022)
Background: Primary lung cancers in India were reported to be rare in earlier studies. But the trend is changing and there is increased incidence of lung cancers. Aims and Objectives: This present descriptive observational study was conducted to report the risk factor profile of the lung cancer patients from the Himalayan state of the Indian population. Materials and Methods: This descriptive epidemiological study was conducted from a single centre, in a prospective observational design, among the patients who were diagnosed as carcinoma lung histologically or cytologically over a period of one year in a tertiary care referral centre in the Himalayan state of the Northern India. The patients data was collected in detailed manner pertaining to age, sex, residence and occupation, questionnaires regarding risk factors like smoking history, Environmental tobacco smoke exposure, Indoor pollution, Alcohol history, HIV infection, Structural lung disease, Religion and Geography. Results: One hundred and one consecutive patients of primary lung cancer were recruited in the study which was confirmed either cytologically or histopathologically. Out of 101 patients, 79 (78.2%) were males and 22 (21.8%) were females, mean age was 62.65 years, 97 (96%) patients had rural background and 4 (4%) patients had urban background, 96 (95.04%) patients were active smokers, 3 (2.9%) were passive smokers and non smokers were 2 (1.9%), 25 (24.8%) were vegetarians and 76 (75.2%) were non vegetarians. 36 patients (35.6%) were from altitude of 0-1000 meters, 41 patients (40.6%) were from altitude of 1001-2000 meters, 21.8% were from altitude of 2001-3000 meters and 2% were from altitude of 3001-4000 meters. Adenocarcinoma was the most common type at all altitudes. Conclusions: Awareness about carcinoma lung in the Himalayan state especially in rural population is still lacking and are presenting at an advanced stage, which largely impact on survival of the patients. This study provides the data pertaining to risk factor profile of the lung cancer patients from the Himalayan state and can be utilised for future comparison with other Indian studies, to educate the community and to spread the awareness of the prevailing lung cancer risk factors.